The Role of Senior High School Experiences in Shaping a Life Project Linked to Higher Education for Students With Disabilities - Rodolfo Cruz-Vadillo; Miguel Ángel Casillas-Alvarado (Universidad Nacional, Costa Rica, 2016)
This article aims to approach the school experiences of 13 students with disabilities. It corresponds to a cross, synchronous and non experimental study, whose scope is mainly descriptive. The data collection was carried out through a semi-structured interview and transcribed from audio recordings to make a category analysis. The main results showed that in the case of students who were born with disabilities, the fact that an institution was inclusive turned out essential for them to have adequate transit through the educational system and thus become apt for higher education. The combination disability-inclusion-right to education-higher education is what this paper aimed to weave, trying to follow as thread or anchor, the previous school experiences of students with disabilities. We recognize that an adequate, inclusive, positive experience besides a subjective construction of the body and disability by family members, become important conditions to access schooling. Education is a right, therefore it can not be seen as an act of charity; it should be required as a quality practice.